Activating cryptic biosynthetic gene cluster through a CRISPR–Cas12a-mediated direct cloning approach. Issue 6 (22nd March 2022) - Liang, Mindong; Liu, Leshi; Xu, Fei; Zeng, Xiaoqian; Wang, Runjun; Yang, Jinling; Wang, Weishan; Karthik, Loganathan; Liu, Jiakun; Yang, Zhiheng; Zhu, Guoliang; Wang, Shuliu; et al.
Abstract: Direct cloning of biosynthetic gene clusters (BGCs) from microbial genomes facilitates natural product-based drug discovery. Here, by combining Cas12a and the advanced features of bacterial artificial chromosome library construction, we developed a fast yet efficient in vitro platform for directly capturing large BGCs, named CAT-FISHING (CRISPR/Cas12a-mediated fast direct biosynthetic gene cluster cloning). As demonstrations, several large BGCs from different actinomycetal genomic DNA samples were efficiently captured by CAT-FISHING, the largest of which was 145 kb with 75% GC content. Furthermore, the directly cloned, 110 kb long, cryptic polyketide encoding BGC from Micromonospora sp. 181 was then heterologously expressed in a Streptomyces chassis. It turned out to be a new macrolactam compound, marinolactam A, which showed promising anticancer activity. Our results indicate that CAT-FISHING is a powerful method for complicated BGC cloning, and we believe that it would be an important asset to the entire community of natural product-based drug discovery.